Coupons and state tobacco policy context as predictors of tobacco use among those reporting e-cigarette use in the U.S.: Findings from the Population Assessment of Tobacco and Health (PATH) Study waves 5–6 (2018–2021) - J.H. Kingsbury; H.L. Kimmel; M.J. Parks; M.R. Creamer; C. Blanco; W.M. Compton (Preventive Medicine Reports)
Background: Receipt of cigarette and e-cigarette coupons predicts initiation and progression of use and hinders cessation. Less is known about how coupons operate in different tobacco regulatory environments. The current study utilized longitudinal data from the Population Assessment of Tobacco and Health (PATH) Study to address this research gap. Methods: Adults who reported past 30-day (P30D) e-cigarette use at Wave 5 (2018–2019) were included (N = 3632). The primary outcome was Wave 6 (2021) P30D any tobacco use. Wave 5 predictors were receipt of e-cigarette coupons, state e-cigarette tax, state tobacco policy context, flavored e-cigarette use, income, and education. Covariates were age, sex, race, state coupon policy, and Wave 5 use of tobacco other than e-cigarettes. Weighted logistic regression models examined effects overall and in samples stratified by state e-cigarette tax and tobacco policy context. Results: Controlling for covariates, Wave 5 coupon receipt (AOR = 1.57; 95 % CI: 1.07, 2.31) and preference for flavored e-cigarettes (AOR = 1.70; 1.37, 2.10) were positively associated with Wave 6 tobacco use. Stronger state tobacco policy context was negatively associated with tobacco use (AOR = 0.69; 0.55, 0.88). Coupon receipt predicted tobacco use in states with an e-cigarette tax (AOR = 2.39; 1.22, 4.68) and with stronger tobacco policy contexts (AOR = 1.80; 1.07, 3.02), but not in states without an e-cigarette tax (AOR = 1.29; 0.83, 1.99) or with weaker tobacco policy contexts (AOR = 1.33; 0.78, 2.24). Conclusions: Policies that restrict price-discounting could help discourage e-cigarette use, reinforce e-cigarette taxes and other tobacco control policies, and promote cessation of all tobacco among those reporting e-cigarette use.